Cross-National Differences in Charitable Giving in the West and the World - Einolf, Christopher J. (Voluntas (Manchester, England), 2017)
Most theories of cross-national variation in charitable giving have been tested only on samples of countries of Western European culture; this paper applies these theories to 114 countries, including 93 non-Western countries, using data from the Gallup World Poll. It finds strong support for economic and political theories of cross-national variation in charitable giving and partial support for religious and cultural theories. Theories effectively predict variation in giving in middle income non-Western countries but poorly predict variation in low-income non-Western countries. This suggests that economic development, not cultural or religious differences, separate non-Western countries from Western ones in patterns of giving behavior. La plupart des théories sur les écarts entre les dons de bienfaisance de divers pays ont été comparées à des échantillons de pays à culture ouest-européenne. Cet article applique ces théories à 114 nations, dont 93 non occidentales, à l'aide de données du sondage Gallup mondial. Il y décèle un fort appui pour les théories économiques et politiques d'écarts entre les dons de bienfaisance de divers pays et un appui partiel envers les théories religieuses et culturelles. Les théories prévoient efficacement les écarts entre les dons fournis par des pays non occidentaux à revenu moyen, tandis que les prédictions sont médiocres pour les pays non occidentaux à faible revenu. Cela suggère que le développement économique, et non les différences culturelles ou religieuses, distingue le comportement des pays non occidentaux des nations occidentales en matière de don de bienfaisance. Die Mehrzahl der Theorien zu länderübergreifenden Unterschieden bei gemeinnützigen Spenden wurde nur anhand von Stichproben aus Ländern mit westeuropäischer Kultur getestet. Dieser Beitrag wendet die Theorien auf 114 Länder, einschließlich 93 nicht-westlicher Länder, an, wobei Daten aus der Gallup World Poll zugrunde gelegt werden. Man sieht deutliche Belege für die ökonomischen und politischen Theorien zu länderübergreifenden Unterschieden bei gemeinnützigen Spenden und eine teilweise Bestätigung der religiösen und kulturellen Theorien. Die Theorien prognostizieren effektiv die Unterschiede im Spendenverhalten in nicht-westlichen Ländern mit mittlerem Einkommen, geben jedoch eine mangelhafte Prognose zu den Unterschieden in nicht-westlichen Ländern mit geringem Einkommen ab. Dies lässt darauf schließen, dass die wirtschaftliche Entwicklung, und nicht die kulturellen oder religiösen Differenzen, nicht-westliche von westlichen Ländern im Bezug auf das Spendenverhalten unterscheiden. La mayoria de las teorías de variación transnacional en la donación benèfica han sido probadas solamente en muestras de países con cultura europea occidental; el presente documento aplica estas teorías a 114 paises, incluidos 83 países no occidentales, utilizando datos de la Encuesta Mundial Gallup. Se encuentra un fuerte soporte para las teorías económicas y políticas de variación transnacional en la donación benèfica y un soporte parcial para las teorías religiosas y culturales. Las teorias predicen de manera efectiva la variación en la donación en el caso de ingresos medios en países no occidentales pero predicen pesimamente la variación en países no occidentales con bajos ingresos. Esto sugiere que el desarrollo econmico y no las diferencias culturales religiosas, separan a los paises no occidentales de los occidentales en los patrones de comportamiento a la hora de realizar donaciones.